(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s processed food sector has expanded dramatically, driven by urbanization, rising incomes, and convenience demands. Food additives substances intentionally added to enhance flavor, color, preservation, or texture play a central role in ultra-processed foods (UPFs). While many are regulated by the Food Safety and Standards Authority of India (FSSAI) with Acceptable Daily Intake (ADI) limits, evidence from global and emerging Indian studies links excessive or improper use of certain synthetic additives to increased risks of non-communicable diseases (NCDs), including type 2 diabetes, various cancers, obesity, allergies, hyperactivity in children and endocrine disruption. This paper examines these threats in the Indian context, drawing on regulatory frameworks, scientific studies, and prevalent practices.